Study on "designing in-house brand for FOKUS Convenience Store" / Roshidah Abdul Wahab - Abdul Wahab, Roshidah (1998)
FOKUS Convenience Store is one of FOKUS Banner Store, a new franchise store introduced by NRC DISTRIBUTION Sdn. Bhd. through its subsidiary NRC Consultancy Sdn. Bhd. FOKUS Convenience Store didn't have its own brand. So this research is carried out to fulfil three objectives that are; to find the important of FOKUS to have in-house brand, to know what product is suitable for the brand, and to determine the factors that will contribute to the success of the in-house brand. From the research, it was found that FOKUS should have its own brand as one of promotion tools and to create customer loyalty. The merchandise that suitable for FOKUS in-house brand are foods and drinks, rice, and sugar and flour. It was also found that the factors that will contribute to the success of the brand are quality, merchandise category, and promotion.